RELIGIOUS NATURALISM IN CHAN BUDDHISM WITH SPECIAL REFERENCE TO THE BLUE CLIFF RECORD - Wang, Baoyu; Beliatte, Metteyya (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2024)
This paper delves into the interplay of religious naturalism and Chan Buddhism, emphasizing its manifestation within the Blue Cliff Record. Beginning with a contextualization of the research, the study identifies a gap in the comprehension of naturalism in this seminal text. Religious naturalism is conceptualized as the belief in nature's entirety, negating the need for the supernatural. By comparing religious naturalism with Buddhist tenets, parallels emerge, particularly the shared accentuation on nature, experiential understanding, and non-dualism. The Blue Cliff Record, a creation under Chan Master Yuanwu Keqin from the Song Dynasty, emphasizes tenets such as the renunciation of attachments and the appreciation of inherent Buddha-nature. A significant portion of the analysis is dedicated to the portrayal of flowers within the text, symbolizing principles harmonious with religious naturalism, including simplicity and self-realization through lived experiences. The dissertation concludes by revisiting its objectives, accentuating the nuanced differences between religious naturalism and Chan Buddhism, and emphasizing the potential for future interdisciplinary dialogues and research.